Behavioral problems in school children as recognized by untrained teachers (Journal of Psychiatrists' Association of Nepal, 2014)
Introduction: Behavior problems in a student at school interfere with his lessons and may disturb other students. In spite of teacher’s best effort, not all children rise up to the expectations. Behavioral problems are a major challenge for teachers. This study was undertaken with the aim of looking into the awareness of teachers into the existence of psychological problems in their students and to find out the type of problem present in the student. Materials and Method: This study was conducted in various districts of western region when the primary author was conducting teachers training for mental health project during the period of 2001 to 2003. Questionnaire developed during the first stage of research was used in the second part. Semi-structured interview was done with 212 teachers (from Eastern Terai, Western Terai and the mid hills) dealing with 23,320 students to find the different symptoms suggesting emotional and behavioural problem. Results:Out of the total 23320 students indirectly covered in the study, 8999 (38.58%) were found to have some sort of psychological problem. ‘Slow learners’ was reported to be present by 77.83% of teachers in 4.98% of their students, suddenly degrading school performance was reported by 75% of teachers in 3.65% of students.Conclusion: An average school teacher in Nepalese government schools can identify behavioural problems in their classroom.   DOI: http://dx.doi.org/10.3126/jpan.v2i2.9722 J Psychiatrists’ Association of Nepal Vol.2, No.2, 2013 26-28